Resenhas - Reflexão (Reflexão, 2007)
LECOURT, Dominique. Humano Pós-humano: a técnica e a vida. Trad. Luiz Paulo Rouanet. São Paulo: Loyola, 2005.. PINHO, Romana Valente. O essencial sobre Agostinho da Silva. Lisboa, Imprensa Nacional, 2006, 95 p.